Design and implementation of an S-band transmitter for nanosatellites with new configuration - Bui Thi Ha; Tran Chinh Doan; Bach Gia Duong (Institute of Advanced Engineering and Science, 2022)
In this paper, the author presents the design and implementation of an Sband transmitter for nanosatellites. By combining heterostructure field effect transistors (HFET) and laterally diffused metal–oxide–semiconductor (LDMOS) technology and using flexible structure and flexible control method, this research obtained 60 dB gain power when input is -14 dBm, output power is 46 dBm (more than 25 W) in 2,1 GHz -2,3 Ghz frequency; phase noise is -80 dBc/Hz at 100 KHz offset frequency. Unlike other traditional transmitters, this transmitter was designed with multi-stages which have multi-peaks resonance to expand bandwidth to respond to the requirement of generation of the complex signal in wide band. Moreover, the phase locked loop (PLL) in frequency synthesizer makes the frequency conversion more flexible and output frequency more stable; thermal problem in module also was solved by using thermistor and operation mode. Measurement results prove that the design does not only satisfy the requirements of nanosatellites but also can be applied to other satellites together with their ground station because it has open configure with flexible structure and flexible control method.